2002
DOI: 10.1007/s00299-002-0517-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the nuclear and cytoplasmic genomes of intergeneric diploid plants from cell fusion between Microcitrus papuana and Rough lemon

Abstract: Simple-sequence-repeat (SSR) and PCR-RFLP were employed to characterize the nuclear and cytoplasmic genomes of intergeneric diploid plants derived from symmetric fusion between Microcitrus papuana Swingle and Rough lemon (Citrus jambhiri Lush). Three out of five SSR primers distinguished the fusion parents from each other and the regenerated plants showed band profiles completely identical to the leaf parent, Rough lemon. Amplified products from the intergenic regions of cpDNA between trnD-trnT were digested w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…In addition, CAPS analysis with the primer pair/enzyme combinations used could not identify the origin of the cytoplasmic genomes in the G1 + Sunburst and G1 + Orie Lee diploid regenerates due to the close phylogenetic relatedness of both fusion parents, although they were thought to be cybrid plants. CAPS analysis has only recently been applied to identify the cytoplasmic inheritance of somatic hybrids in higher plants and has proven to be very efficient (Bastia et al 2001;Guo et al 2002;Liu et al 2002;Cheng et al 2003a;Lotfy et al 2003). Chloroplast microsatellite (cp-SSR) analysis is a new tool for plant ecology and evolution studies (Provan et al 2001) and has only recently been introduced into citrus phylogenetic study (Cheng et al 2003b).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, CAPS analysis with the primer pair/enzyme combinations used could not identify the origin of the cytoplasmic genomes in the G1 + Sunburst and G1 + Orie Lee diploid regenerates due to the close phylogenetic relatedness of both fusion parents, although they were thought to be cybrid plants. CAPS analysis has only recently been applied to identify the cytoplasmic inheritance of somatic hybrids in higher plants and has proven to be very efficient (Bastia et al 2001;Guo et al 2002;Liu et al 2002;Cheng et al 2003a;Lotfy et al 2003). Chloroplast microsatellite (cp-SSR) analysis is a new tool for plant ecology and evolution studies (Provan et al 2001) and has only recently been introduced into citrus phylogenetic study (Cheng et al 2003b).…”
Section: Resultsmentioning
confidence: 99%
“…CAPS is simple, more rapid and less expensive when compared to the direct analysis of restricted cp-and mt-DNA. In citrus, CAPS markers were employed to characterize the cp-and mt-DNA of somatic hybrids or cybrids between Microcitrus papuana and Citrus jambhiri (Liu et al 2002), Citrus reticulata and Poncirus trifoliata , and C. sinensis and F. crassifolia (Cheng et al 2003). In the present study, cp-and mt-DNA analyses using CAPS markers revealed that cp-and mt-DNA of the somatic hybrids were derived from round kumquat without recombination in the regions analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…In Citrus and related species, somatic hybridization techniques are well developed and have been employed to facilitate improvement of Citrus scion and root stock (Grosser and Chandler 2000;. To date, more than 150 citrus somatic hybrids have been produced throughout the world, including intergeneric combinations (Moreira et al 2000;Guo et al 2002;Liu et al 2002). However, only a few somatic hybrids have been produced between Fortunella and Citrus species, i.e., Meiwa kumquat with sweet orange (Deng et al 1992;Shi et al 1998;Cheng et al 2003), Meiwa kumquat with 'Succari' sweet orange (Grosser et al 1996), round kumquat with Mediterranean mandarin (Ollitrault et al 1996), and Kinzu kumquat with trifoliate orange (Miranda et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…de combinações interespecíficas (Liu et al, 2002). Embora a formação de cíbridos através de hibridação somática em Citrus pareça ocorrer somente em combinações de espécies dentro do gênero (Moriguchi et al, 1996), plantas cíbridas da combinação entre Microcitrus papuana e Citrus aurantium foram obtidas (Xu et al, 2004).…”
Section: Resultsunclassified
“…Análises destas plantas com base em marcadores moleculares têm indicado que as mesmas são híbridos aloplásmicos ou cíbridos, apresentando genoma nuclear do genitor não-embriogênico e o mtDNA do genitor embriogênico (Moreira et al, 2000;Liu et al, 2002).…”
Section: Introductionunclassified